Learning English Grammar Using Conversation Techniques Based On Student Perception - Aspari Aspari; Risa Prayudhi; Titi Dewi Rohati (Sean Institute, 2023)
Learning English grammar using conversational techniques is one way to make it easier for students to understand. This research aims to discover students' perceptions of learning English grammar using informal techniques. The ultimate goal is to determine whether conversational techniques in learning English grammar are good or not to be applied in learning English, especially English grammar lessons. The results of this research are that English students feel comfortable and find it easier to learn English grammar using conversational techniques than lecture techniques and others.